Marriage and fatherhood in the Nazi SS - Carney, Amy Beth (Toronto Buffalo ; London : University of Toronto Press, 2018)
"From 1931 to 1945, leaders of the SS, a paramilitary group under the Nazi party, sought to transform their organization into a racially-elite family community that would serve as the Third Reich's new aristocracy. They utilized the science of eugenics to convince SS men to marry suitable wives and have many children. Marriage and Fatherhood in the Nazi SS, by Amy Carney, is the first work to significantly assess the role of SS men as husbands and fathers during the Third Reich. The family community, and the place of men in this community, started with one simple order issued by SS leader Heinrich Himmler. He and other SS leaders continued to develop the family community throughout the 1930s, and not even the Second World War deterred them from pursing their racial ambitions. Carney's insight into the eugenic-based measures used to encourage SS men to marry and to establish families sheds new light on their responsibilities not only as soldiers, but as husbands and fathers as well."--
Cover; Page i; Copyright; Contents; List of Illustrations; Acknowledgments; Introduction; 1 The Engagement and Marriage Command; 2 Establishing SS Families; 3 Marriage during the Second World War; 4 Sustaining the Family Community during the War; 5 Belonging to the Family Community; 6 Assessing SS Population Politics and the Family Community; Appendices; Appendix A: The Engagement and Marriage Command; Appendix B: Development of the SS; Appendix C: Rank Comparisons; Appendix D: Organization of the Allgemeine-SS; Notes; Bibliography; Index
Description based on online resource; title from digital title page (viewed on March 5, 2024).
Includes bibliographical references (pages 261-299) and index.
In English.
JSTOR
Keywords: Nationalsozialistische Deutsche Arbeiter-Partei. -- Schutzstaffel; Nationalsozialistische Deutsche Arbeiter-Partei. -- Schutzstaffel; Mishnah; Family policy -- Germany -- History -- 20th century; Fatherhood -- Germany -- History -- 20th century; Marriage -- Germany -- History -- 20th century; Politique familiale -- Allemagne -- Histoire -- 20e siècle.; Paternité -- Allemagne -- Histoire -- 20e siècle.; Mariage -- Allemagne -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; HISTORY / Europe / Germany; Family policy; Fatherhood; Marriage; Germany; 1900-1999; History